Complement set focus after positive quantifiers: The influence of context - Poirier Rachel C.; Upadhyay Sri Siddhi N.; Klin Celia M. (Psychology of Language and Communication, 2025)
During reading, different cues influence readers’ focus. One of these is natural language quantifiers. Negative quantifiers, such as few (e.g., “Few attended the lecture”), have a complex influence on focus. They convey a sense of shortfall – a quantity that is less than what was expected (e.g. Moxey, 2006; Moxey & Sanford, 1987). This, in turn creates focus on the complement set (e.g., those not attending). Upadhyay et al. (2018) demonstrated the influence of story context on these focus effects. In three experiments, we investigated the influence of story context on focus effects with positive quantifiers. Although positive quantifiers are less diffuse in their meaning than negative quantifiers, context can lead positive quantifiers to convey shortfall, as negative quantifiers do. When the story context creates an expectation for a large quantity (e.g., many), the positive quantifier a few was understood as shortfall, leading to focus on the complement set.